Influence of Vertebrobasilar Stenotic Lesion Rigidity on the Outcome of Angioplasty and Stenting - Chang, Feng-Chi (Sci Rep, 2020)
Stenotic lesion rigidity (SLR) has an unclear influence on the outcome of percutaneous transluminal angioplasty and stenting (PTAS) for intracranial arterial stenosis. This study evaluated the outcome of PTAS and the relationship of vertebrobasilar SLR to features on vessel wall MRI (VW-MRI) for identifying pathologies of vertebrobasilar stenosis (VBS) and evaluating PTAS outcome. We retrospectively evaluated the results of PTAS in 31 patients with severe VBS. Stenotic lesions were classified as soft (based on predilatation pressure [PP] ≦ 4 atm) in 15 patients or hard (PP >4 atm) in 16 patients. We examined the relationship of SLR to clinical and MR findings. Patients with hard vs soft lesions had atherosclerosis (8/16 [50.0%] vs 2/15 [13.3%]), dissection (0/16 [0.0%] vs 12/15 [80.0%]), and dissection in atherosclerosis (8/16 [50.0%] vs 1/15 [6.7%], P < 0.0001); high intensity signal on the T1WI of VW-MRI (5/16 [31.3%] vs 14/15 [93.3%]) and iso- to low intensity signal (11/16 [68.7%] vs 1/15 [6.7], P = 0.001), and significant in-stent restenosis (>50%) in 5/15 (33.3%) vs 0/15 (0.0%) (P = 0.0421) in the 30 patients who successfully completed PTAS. Vertebrobasilar SLR correlated well with lesion etiology, findings on VW-MRI, and PTAS outcome. Patients with hard stenotic lesions need close follow-up after PTAS.